Faktor-Faktor Terjadinya Stunting pada Balita: Scoping Review - Irma S. Yuniar; Fita C. Laiga; Nurfadilah Kemhay; Fajrin T. Astuti4; Nurmeylan Jacobus; Risni S. Mauri; Anggun Sasmita (Jurnal Ventilator, 2024)
Stunting is a growth disorder due to malnutrition that occurs in children under five years old. Stunting in children under five is a consequence of several factors that are often associated with poverty, including nutrition, health, knowledge and social and cultural factors. The aim of this research is to look at the factors that cause stunting in toddlers. The research method uses Scoping Review to map literature and identify problems or shadows in the research area to be studied. The results of the research show that data obtained that the number of stunting cases in Jorong Lubuk Sao can be worrying, the results of the data show that there is an average for each stunting indicator (TB, BB, LK) which indicates stunting. The intervention that has been carried out from the data above is by providing outreach and counseling regarding healthy food as well as introducing the electronic application ready for marriage and pregnancy (elsimil) to the local community, this is an accompanying screening application for prospective brides (catin), prospective couples of childbearing age (CaPUS) , pregnant women, postpartum mothers, and families with babies aged 0-59 months. The conclusion of this research is that the stunting prevalence rate in Indonesia is still above 20%, meaning it has not reached the WHO target. Influencing factors are low levels of exclusive breastfeeding, low protein energy intake, poor provision of MP-ASI, low family income, completeness of immunizations.